Multi-omics reveals the alleviating effect of berberine on ulcerative colitis through modulating the gut microbiome and bile acid metabolism in the gut-liver axis - Yu, Jingsheng; Zheng, Yixuan; Liu, Changmin; Xie, Zhuangyuan; Liu, Qingqing; Yang, Shuai; Tian, Qianqian; Song, Chi; Chen, Shilin (Frontiers in Pharmacology, 2024)
The dysfunction of gut microbiome and bile acid metabolism might cause the incidence and relapse of ulcerative colitis (UC). Thus, natural products have been considered effective for UC through the regulation of gut microbiome and bile acid. In this study, we evaluated the regulatory effect of berberine on gut microbiome and bile acid metabolism in UC. Results showed that the relative abundances of beneficial bacteria showed a decreasing trend in the UC model, and the taurine conjugated bile acids increased from the liver tissue to the colon tissue. Berberine inhibited the colonization of harmful bacteria and promoted the primary bile acid metabolism. Moreover, we used multi-omics technology (metagenomics, metabolomics, and transcriptomics technology) to reveal that berberine restored the intestinal barrier function through bile acid/S1PR2/RhoA/ROCK pathway. The result of transmission electron microscopy directly showed that the damaged intestinal mucosal barrier was repaired through the berberine treatment. This study revealed the treatment influence on UC through multi-omics technology in vitro and in vivo models, which provides references for explaining the mechanism of berberine on UC.